Case Report of Complete Radiological Response of a Thalamic Glioblastoma After Treatment With Proton Therapy Followed by Temozolomide and Tumor-Treating Fields - Stein, Marco; Dohmen, Hildegard; Wölk, Bernhard; Eberle, Fabian; Kolodziej, Malgorzata; Acker, Till; Uhl, Eberhard; Jensen, Alexandra (Frontiers in Oncology, 2020)
Glioblastoma (GBM) is the most common and aggressive primary brain tumor in adults. We present a case of a 42-year-old male patient presenting with headache and vomiting. Imaging demonstrated obstructive hydrocephalus and a ring enhancing lesion in the right posterior thalamus. After endoscopic third ventriculostomy and stereotactic biopsy the histopathological diagnosis of a malignant glioma was confirmed by DNA methylation array as GBM isocitrate dehydrogenase (IDH) wildtype. The patient was treated with combined treatment of chemoradiation with temozolomide (TMZ) including proton boost, TMZ maintenance, and Tumor Treating Fields (TTFields). In this case report complete radiological response was observed one year after the end of radiation therapy.